Social Media, Depressive Symptoms and Well-Being in Early Adolescence. The Moderating Role of Emotional Self-Efficacy and Gender - Calandri, Emanuela; Graziano, Federica; Rollé, Luca (Frontiers in Psychology, 2021)
The study of the psychological effects of social media use on adolescents’ adjustment has long been the focus of psychological research, but results are still inconclusive. In particular, there is a lack of research on the positive and negative developmental outcomes and on possible moderating variables, especially concerning early adolescence. To fill these gaps in literature, the present study longitudinally investigated the relationships between social media use, depressive symptoms, affective well-being and life satisfaction, as well as the moderating role of emotional self-efficacy and gender. The study involved 336 Italian early adolescents (mean age = 13, sd = 0.3; 48% girls) who completed an anonymous self-report questionnaire twice within a year. Main results showed that higher social media use was related to higher depressive symptoms, lower affective well-being and lower life satisfaction among girls with lower emotional self-efficacy. Conversely, high social media use was related to higher affective well-being and higher life satisfaction for girls with higher emotional self-efficacy. Results are discussed in relation to their implications for risk prevention and health promotion among early adolescents. In particular, our results suggest that promoting emotional self-efficacy can be very helpful in making the use of social media an opportunity for well-being and life satisfaction rather than a developmental risk.